(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The causes, pathogenesis and consequences of secondary brain damage in patients with intracranial hemorrhages are described. It is shown that with increasing edema and acute prolapse of the brain after removal of the foci of damage, the only method of treatment is decompressive craniotomy (DC). Indications and contraindications for DC are listed. Special attention is paid to the technical features of DC. It is emphasized that timely and, if possible, early implementation of DC contributes to a reliable improvement in the treatment outcomes of victims with severe TBI